Inhabitant actions and summer overheating risk in London dwellings. Issue 1 (17th February 2017) - Mavrogianni, Anna; Pathan, Ayub; Oikonomou, Eleni; Biddulph, Phill; Symonds, Phil; Davies, Mike
ABSTRACT: An indoor overheating assessment study of 101 London dwellings during summer 2009 is presented. The study included building surveys, indoor dry bulb temperature monitoring and a questionnaire survey on occupant behaviour, including the operation of passive and active ventilation, cooling and shading systems. A theoretical London housing stock comprising 3456 combinations of building geometry, orientations, urban patterns, fabric retrofit and external weather was simulated using the EnergyPlus thermal modelling software. A statistical meta-model of EnergyPlus was then built by regressing the independent variables (simulation input) against the dependent variables (overheating risk). The monitoring and questionnaire data were analysed to explore the relationship between self-reported behaviour and overheating, and to test the meta-model. The monitoring data indicated that London homes and, in particular, bedrooms are already at risk of overheating during hot spells under the current climate. Around 70% of respondents tended to open only one or no windows at night mainly due to security reasons. An improvement in the coefficient of determination ( R 2 ) values between measured temperature and meta-model predictions was obtained only for those dwellings where occupants reported actions that were in line with the modelling assumptions, thus highlighting the importance of occupant behaviour for overheating.